Universidade itinerante - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The Federal University of Pampa is a multicampi higher education institution. which aims at regional development through education, offering free education and Of Quality. However, this social role needs to be publicized in city schools where the campuses are located. According to Silva & Vasconcelos (2006), the role transforming university extension can only be established as a praxis of a public university when professors, students, technical-administrative staff and managers commit to transforming the educational reality Brazilian. The university needs to be present in the community, as families and schools need help to encourage children and adolescents to follow. studying and to have a goal of professional training. According to Sousa and José Son (2006), the construction of a social being, that is, the student, must have a relationship between teaching-learning and the formation of citizens. One of the biggest obstacles in this construction is that the school and teachers are devalued by society and of governments and this devaluation causes a break in the necessary link for the social formation of the student. The student realizes this fact, even disclosed by some media, which denigrate the teacher's image, which ends up discrediting the professional. Society needs to be aware that the school does not will perform this role without the action of the family and families are constituted by values, regional principles and traditions.At this point, the university enters, which must maintain close relations with the community, including with other levels of education. The university needs to be present in schools, reflecting and showing students that there are several functions and professions that can be pursued, and even that there is an academic career. THE academic journey starts at school and needs to be continued, whether at a technical level or higher. In this context, the university community of the Campus Itaqui of UNIPAMPA developed the Itinerant University Project with local high schools. Through it, we sought to motivate students to continue their studies after the completion of high school, aiming for a profession and citizenship education. AND mainly to disclose that UNIPAMPA is a free federal university, and that all to those who want and who pass the National High School Exam (ENEM), can occupy a place in the undergraduate courses offered. Finally, this extension action is intended to complement the training academic and professional students of the courses of Campus Itaqui/UNIPAMPA, making them have experiences and experiences that can show the social reality, contributing to their future professional, citizen and humane performance. From this perspective, the general objective of this work was to carry out the integration between the university and high schools in the city of Itaqui - RS, promoting the dissemination of undergraduate courses and teaching and research projects and extension that are developed at Campus Itaqui/UNIPAMPA. The specific objectives of the project were: To publicize the Undergraduate Courses of the Itaqui/UNIPAMPA Campus; Recognize the importance in the citizen formation of students of the Undergraduate Courses of Campus Itaqui, with the interaction between different levels of education and social reality; Valuing professional training with elementary and high school students; Valuing elementary and high school education encouraging students to permanence and continue their studies and to see the Undergraduate Courses at the Itaqui/UNIPAMPA Campus as an opportunity to professional qualification; Bringing the University to the community by spreading the word free of charge in higher education and that all citizens can attend one of the graduations of the Itaqui/UNIPAMPA Campus.
Traveling university
Keywords: Educação; Ciências humanas; Ensino; Ensino médio; Education; Human sciences; High school; CNPQ::CIENCIAS HUMANAS